THE USE OF MAJAZ IN HADITH TEXTS: A Systematic Literature Review of Contextual Interpretation and Linguistic Analysis - Hidayati, Eni; Marhumah, Marhumah; Syaifuddin, Najamudin Dano; Nadhifa, Hasna Putri (RIWAYAH, 2025)
The use of majaz (figurative language) in hadith texts has long been recognized as an important element in understanding the linguistic depth and contextual meaning of the Prophet Muhammad’s sayings. However, studies on this topic have generally focused on majaz within theoretical or semantic discourse, without providing a systematic mapping of its methodological role and socio-religious implications. This study aims to fill this gap by employing a Systematic Literature Review (SLR) method following the PRISMA protocol, examining 36 scholarly articles on majaz in hadith published between 2019 and 2025. The review focuses on publication trends, dominant methodological approaches, geographical distribution of research, and the implications of majaz for contextual interpretation and contemporary Muslim life. The findings reveal a significant increase in academic interest during the period 2021–2024, marked by a strong dominance of qualitative, linguistic, and contextual approaches, particularly those integrating balaghah, semantics, socio-historical analysis, and hermeneutics. Majaz is increasingly positioned not merely as a rhetorical device but as a substantive interpretive instrument with important implications for legal reasoning, ethical formation, and socio-religious construction. Nevertheless, a gap remains between the theoretical recognition of majaz and its application in religious practice, education, and public policy, largely influenced by the persistence of conservative literalist paradigms. This study offers both methodological and thematic novelty by systematically mapping the role of majaz in hadith studies and positioning it as a bridge between textual fidelity and contemporary relevance, thereby supporting the development of a more adaptive, interdisciplinary, and context-sensitive methodology in hadith scholarship. [Penggunaan majaz (bahasa figuratif) dalam teks-teks hadis telah lama diakui sebagai unsur penting dalam memahami kedalaman linguistik dan makna kontekstual sabda Nabi Saw. Namun, kajian-kajian terhadapnya selalu fokus pada diskursus majaz yang menekankan pada aspek teoretis atau semantik, tanpa pemetaan yang sistematis terhadap peran metodologis dan implikasi sosio-keagamaannya. Penelitian ini bertujuan untuk mengisi celah tersebut dengan menerapkan metode Systematic Literature Review (SLR) yang mengikuti protokol PRISMA, terhadap 36 artikel ilmiah tentang majaz dalam hadis yang dipublikasikan antara tahun 2019–2025. Kajian ini berfokus pada tren publikasi, pendekatan metodologis yang dominan, distribusi geografis penelitian, serta implikasi majaz terhadap penafsiran kontekstual dan kehidupan Muslim kontemporer. Hasil penelitian menunjukkan adanya peningkatan signifikan minat akademik pada periode 2021–2024, dengan dominasi kuat pendekatan kualitatif, linguistik, dan kontekstual, terutama yang mengintegrasikan balaghah, semantik, analisis sosio-historis, dan hermeneutika. Majaz semakin diposisikan bukan sekadar sebagai perangkat retorika, melainkan sebagai instrumen penafsiran substantif yang memiliki implikasi penting terhadap penalaran hukum, pembentukan etika, dan konstruksi sosial-keagamaan. Meskipun demikian, masih terdapat kesenjangan antara pengakuan teoretis terhadap majaz dan penerapannya dalam praktik keagamaan, pendidikan, dan kebijakan publik, yang sebagian besar dipengaruhi oleh kuatnya paradigma literalistik-konservatif. Studi ini memberikan kebaruan metodologis dan tematik dengan memetakan secara sistematis peran majaz dalam studi hadis, serta menempatkannya sebagai penghubung antara kesetiaan terhadap teks dan relevansinya terhadap konteks kontemporer, sehingga mendukung pengembangan metodologi kajian hadis yang lebih adaptif, interdisipliner, dan peka terhadap konteks.]